Exploration of Business Model of Intangible Cultural Heritage Culture Based on Rural Revitalization Strategy: A Case Study of Fuyang Embroidery - Tan, Huiqin; Gu, Xiaoying; Hu, Yashi; Li, Deyu (International Journal of Social Sciences and Public Administration, 2023)
As an intangible cultural heritage of Anhui Province, Fuyang embroidery has strong local characteristics and aesthetic value. However, due to the transformation of modern aesthetic needs, the impact of mechanized large-scale production and other factors, the market-oriented operation of Fuyang embroidery is difficult and declined. With the party and the country’s emphasis on intangible cultural heritage and the emphasis on the inheritance and innovation of intangible cultural heritage, it provides new ideas for Fuyang embroidery. Therefore, this paper explores the business model of Fuyang embroidery based on the rural revitalization strategy, from the Internet+ professional platform exhibition, digital promotion, and cultural core connotation The four aspects of financial support are discussed in order to provide a development path for the commercial operation of Fuyang embroidery and realize the connection between tradition and modernity.